Implementation of Overpressure-Retort Technology to Extend Shelf Life of Packaged Rendang Products in West Pasaman - Rizki Dwi Setiawan; Indri Juliyarsi; Surya Aulia H (Indonesian Scientific Journal, 2026)
Rendang producers at the Rendang Bu Pit MSME face a short ambient shelf life due to the absence of thermal sterilization, which constrains distribution and undermines product consistency. This community service program aimed to implement overpressure retort sterilization to improve product quality and extend shelf life. Methods included partner engagement, training on retort principles, familiarization with critical parameters, installation and commissioning of the unit, temperature-distribution and heat-penetration tests, and pilot production runs. Implementation yielded actionable process control: sterilization of 250-g beef and clam rendang achieved commercial sterility (F > 3) in compliance with national requirements while preserving pouch integrity through overpressure cooling; the partner also initiated systematic cycle documentation and basic F calculations. These outcomes delineate a pathway to extend shelf life toward a six-month target at room temperature, strengthen production readiness, and broaden market access.